Salivary total α-synuclein, oligomeric α-synuclein and SNCA variants in Parkinson’s disease patients - Kang, Wenyan (Sci Rep, 2016)
The present study was to evaluate the diagnostic value of salivary total and oligomeric α-synuclein levels in PD. Furthermore, we sought to explore the relationship between salivary total α-synuclein and α-synuclein SNP variants levels. 201 PD patients and 67 controls were recruited, of which there also had the genetic information of two positive α-synuclein (SNCA) loci. Salivary total α-synuclein was assayed using a highly sensitive Luminex assay and oligomeric α-synuclein was quantified by the combination of Gel filtration chromatography and Western blot, respectively. From our analysis,No difference in salivary total α-synuclein levels was found between PD patients and healthy controls, it decreased with age in PD patients, and was closely associated with genotypic distribution of rs11931074 and rs894278 in PD, respectively. After controlled for age and genders, G allele of rs11931074 was correlated with lower salivary total α-synuclein levels, while G allele of rs894278 was also correlated with the higher levels. Simultaneously, the further study was shown that salivary oligomeric α-synuclein in PD patients significantly increased comparing to healthy controls. In conclusions,our study firstly demonstrated that salivary total α-synuclein levels could be manipulated by different α-synuclein SNPs and salivary oligomeric α-synuclein could be a potential diagnostic indicator of PD.